Santripreneurship: Model Kemandirian Ekonomi Berbasis Pesantren di Era Digital - Wirdatul Khomro Septian Candra; Eka Putri Wulandari; Aisyah Asri Nurrahma (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Islamic boarding schools (pesantren) hold substantial potential in advancing Islamic value-based economic development; however, many students (santri) remain unfamiliar with entrepreneurship concepts and practices that could strengthen their financial independence. This study aims to cultivate students' entrepreneurial spirit through a community service program titled Santripreneurship: Training Students to Be Independent, conducted at Hamalatul Quran Al-Karimah Islamic Boarding School, Pare, Kediri, East Java. The implementation method included observation, preparation, socialization, and Focus Group Discussions (FGDs), with the Business Model Canvas (BMC) applied as a structured tool for business idea development. Using a participatory approach, students were guided to identify business opportunities within the pesantren environment, define target market segments, and draft simple business strategies grounded in Islamic principles. Results showed an increase in students' entrepreneurial knowledge, improved capacity to construct basic business models, and the emergence of concrete business ideas — including healthy juice production and bicycle rental services around the English Village (Kampung Inggris) area. The program also built students' awareness that entrepreneurship carries both spiritual and social dimensions. The Santripreneurship training proved effective in fostering student independence and reinforcing the pesantren's role as a center for Islamic-based economic empowerment.